Use of Mobile Technologies by Law Students in the Law Library: a Detailed Investigation. (March 2020) - Abbas, Zaki; MacFarlane, Andrew; Robinson, Lyn
Abstract: This paper follows up from a previous study on this topic and outlines the second part of a wider, two-part study on the information seeking behaviour (ISB) of law students. Exploratory work was outlined in a previous publication 17 and there we found that although mobile technologies offered benefits to law students seeking information for their academic studies, there was concern from law librarians that the use of electronic resources via both non-mobile and mobile interfaces resulted in a loss of skills required for information retrieval due to the increasing capabilities of electronic resources' search interfaces. To gain more insight into how law students were using mobile information resources, and better understand the advantages and disadvantages of such, we extended our study to a wider cohort and employed more research techniques including a focus group. This final phase of our study was conducted between 2015 to 2017. Here our cohort included another set of law librarians (13) and a further 54 law students. We expanded our research tools to include 2 thematic questionnaires and a focus group exercise. Our findings discovered that law librarians were concerned with the intangibility of digital formats. Law students remained indifferent to this aspect and valued the speed, multi-tasking and near-ubiquitous accessibility attributes that electronic format use via mobile technologies provided. These learnings and more, with conclusions, are reported in the course of this paper written by Zaki Abbas, Andrew MacFarlane and Lyn Robinson.